2023
DOI: 10.3390/healthcare11071021
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Knowing Sign Language and Quality of Life among Italian People Who Are Deaf: A Cross-Sectional Study

Abstract: Deafness is a medical condition with important relational implications. This condition could affect well-being and self-esteem and cause social anxiety. Sign language is not only a simple mimic but can be considered as a different kind of communication that could be protective for those who have learned it. However, some people do not use sign language because they think it can be marginalizing. The present study aimed to compare the quality of life (QoL) between people who learned Italian sign language as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…As an additional benefit, outside the home and school, out in the social world, signing allows a deaf child to enter rich two-way communication encounters, which form the basis for making friends, exchanging information, making jokes, etc. – this is an enormous psycho-social benefit [ 123 ].…”
Section: Advantages Of Early Sign Language Acquisition/learningmentioning
confidence: 99%
“…As an additional benefit, outside the home and school, out in the social world, signing allows a deaf child to enter rich two-way communication encounters, which form the basis for making friends, exchanging information, making jokes, etc. – this is an enormous psycho-social benefit [ 123 ].…”
Section: Advantages Of Early Sign Language Acquisition/learningmentioning
confidence: 99%
“…Hearing-disabled people have numerous communication issues with the rest of the community. Research findings indicate that knowledge of sign language and the availability of sign language interpreters represent one of the indicators of the quality of life from the perception of deaf people [3,4]. Helping the hearing disabled learn the sign language alphabet using interactive computer software or to convert their gestures into computerrecognized alphabets is how SSL software can help with these challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent evidence suggests that sign language supports the proper development of language brain circuits in deaf participants (for recent evidence, see Cheng et al, 2023 ; Wang et al, 2023 ) and sign language proficiency is associated with higher executive functions (e.g., performance in Go/no‐go task, Simon task; Kotowicz et al, 2023 ). Although it has been suggested that knowing sign language can help deaf individuals to feel comfortable and less stressed in social contexts (La Grutta et al, 2023 ), sign language can only be used with other signing individuals and hearing aids and cochlear implants (CIs) may not always work efficiently (e.g., Orji et al, 2020 ). This is especially in case of noisy environments, or when the other person is too distant or does not face the deaf person.…”
Section: Introductionmentioning
confidence: 99%
“…Go/no-go task, Simon task; Kotowicz et al, 2023). Although it has been suggested that knowing sign language can help deaf individuals to feel comfortable and less stressed in social contexts (La Grutta et al, 2023), sign language can only be used with other signing individuals and hearing aids and cochlear implants (CIs) may not always work efficiently (e.g., Orji et al, 2020). This is especially in case of noisy environments, or when the other person is too distant or does not face the deaf person.…”
mentioning
confidence: 99%